2014
DOI: 10.1186/1471-2466-14-104
|View full text |Cite
|
Sign up to set email alerts
|

An autopsy study of combined pulmonary fibrosis and emphysema: correlations among clinical, radiological, and pathological features

Abstract: BackgroundClinical evaluation to differentiate the characteristic features of pulmonary fibrosis and emphysema is often difficult in patients with combined pulmonary fibrosis and emphysema (CPFE), but diagnosis of pulmonary fibrosis is important for evaluating treatment options and the risk of acute exacerbation of interstitial pneumonia of such patients. As far as we know, it is the first report describing a correlation among clinical, radiological, and whole-lung pathological features in an autopsy cases of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 23 publications
1
68
0
2
Order By: Relevance
“…22.8 ), NSIP, desquamative interstitial pneumonia (with extensive fi brosis), respiratory bronchiolitis -associated ILD [ 7 , 19 , 111 -113 , 122 ]. In an autopsy series of 22 cases including 15 (68 %) with a UIP pattern at HRCT -and 19 with lung cancer -, a pathological pattern of UIP was observed in all cases [ 108 ]. Honeycombing coexisting with emphysema was present in half of the patients.…”
Section: Pathologymentioning
confidence: 95%
See 2 more Smart Citations
“…22.8 ), NSIP, desquamative interstitial pneumonia (with extensive fi brosis), respiratory bronchiolitis -associated ILD [ 7 , 19 , 111 -113 , 122 ]. In an autopsy series of 22 cases including 15 (68 %) with a UIP pattern at HRCT -and 19 with lung cancer -, a pathological pattern of UIP was observed in all cases [ 108 ]. Honeycombing coexisting with emphysema was present in half of the patients.…”
Section: Pathologymentioning
confidence: 95%
“…They may be associated or not with typical honeycombing, from which they differ by the larger size of the cysts and their often being not clustered, whereas honeycombing corresponds to clustered, cystic air spaces, 3-10 mm and up to 2.5 cm in diameter [ 107 ]. They may be associated with more extensive emphysema at imaging [ 108 ]. Thick-walled large cysts likely result from the development of pulmonary fi brosis in the setting of emphysematous lung, with enlargement of the cysts due to retraction forces in fi brotic lung [ 99 , 109 ].…”
Section: Thick-walled Large Cystsmentioning
confidence: 96%
See 1 more Smart Citation
“…Not all IIPs with emphysema can be diagnosed by SLB in real life practice, and the clinical features might be different between SLB cases and clinically diagnosed cases. Third, we did not study the pathological features of IPF with emphysema as recently reported by Inomata et al [28]. Fourth, we did not differentiate between centrilobular and paraseptal emphysema.…”
Section: Discussionmentioning
confidence: 99%
“…In the latter group, interobserver agreement on scoring can be poor even amongst experienced thoracic radiologists. The distinction between emphysema and fibrosis on high-resolution computed tomography is expected to be problematic as these two entities are overlapping even on pathology level [20]. Finally, the type of emphysema (paraseptal vs. centrilobular) was not studied.…”
mentioning
confidence: 99%